Etymologie nienaukowe nazw miejscowości w Podaniach i legendach pomorskich Romualda Frydrychowicza - Rogowska-Cybulska, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article describes thirteen folk (unscientific) etymologies of eleven place names included in Romuald Fryderowicz’s 2013 book Podania i legendy pomorskie zebrane w latach 1914–1922 [Pomeranian legends collected in the years 1914–1922]. A folk etymology is defined as ‘scientifically incorrect explanation of the origins of a word based on the similarity of its form to other words or other casual associations’.The analysed pseudo‑etymologies concern the following place names: Borkowo, Górzno, Osie, Przechowo, Rudki, Tleń, Tuchola, Warzno, Wysin, Zawory and Zblewo; the book devotes two pseudo-etymologies to Tuchola and Wysin each. Some of these pseudo etymologies come from a field exploration, but as much as seven of them occur to be pseudo-scientific. The author uses this term for unprofessional (contrary to onomastic methodology) explanations of the structure and meaning of a word using the research results of various scientific disciplines, especially history.